In Search of Literary Love in Malay Literature: The Early Stages of Relationship - Salleh, University Sains Malaysia, Muhammad Haji (Asiatic: IIUM Journal of English Language and Literature, 2011)
The culture of desire, passionate love and marriage is often a main plot in oral and written Malay literary works. However, the emotions that we categorise as love are extremely complex, with their different stages of development. A long list of words refers to this central emotion: â€œBerahi,â€ â€œasyik,â€ â€œasyik berahi,â€ â€œgila asmara,â€ â€œberangta,â€ â€œkendak,â€ â€œkasih,â€ â€œsayang,â€ â€œcintaâ€ and â€œcinta asmaraâ€ (romantic love). Â Â In his study of Victorian novels and paintings, Culture of Love: Victorians to Moderns, Stephen Kern found a process of 18 steps and/ or elements in love. These are waiting, meeting, encounter, embodiment, desire, language, disclosure, kissing, gender, power, others, jealousy, selfhood, proposal, wedding, sex, sexual relations, marriage and ending. In my initial survey of the Malay oral and written hikayats, and poems I am able to fit in most of Kern’s categories. However, because of the differences in cultural and literary perceptions, some are blurred, and some others are absent, replaced still by others. Â Â This paper explores the first four categories, i.e. the first news/ dream, the first peek, the meeting and the verbal lovemaking and illustrates the uniqueness of this concept in Malay literature.